Utilization of flying fish eggs as a protein and fat source in making breast milk substitute food - Syahid, Muhammad Alif Nur; Aqilah, A Talita Zahra; Khairani, A Gadiza; Adrias, Nurul Aqilah Sa’adah; Rimantho, Dedi (Journal of Food Technology Research, 2025)
This study aimed to optimize the use of flying fish eggs by analyzing their fatty acid and amino acid profiles, highlighting their suitability for baby food blends. Flying fish eggs (Exocoetus spp.), commonly known as tobiko, are valuable marine products found in eastern Indonesia, particularly in Sulawesi’s waters, including Takalar. While predominantly used as sushi ingredients, their nutritional potential remains underexplored. Rich in amino acids and protein, research on their fatty acid and amino acid composition is limited. Using ultra-performance liquid chromatography (UPLC), the study identified 22 fatty acids, including 29.71% saturated fatty acids, 7.86% monounsaturated fatty acids, and 13.64% polyunsaturated fatty acids. The protein concentrate contained 15 amino acids, including leucine (5.86%), lysine (3.69%), valine (3.41%), and glutamate (7.08%), among others. Tobiko protein concentrate increased the amount of protein in breast milk and infant formula, showing that it could be used for nutrification purposes. The results of this study show that flying fish eggs are nutritious and could be used in functional foods, especially those for babies. This is a creative way to use an underused marine resource.